Study of milk coagulation induced by chymosin using atomic force microscopy. (June 2019) - Freitas, Cleverson D.T.; Silva, Maria Z.R.; Oliveira, João P.B.; Silva, Ayrles F.B.; Ramos, Márcio V.; de Sousa, Jeanlex S.
Abstract: Caseins (αs1 -, αs2, β-, and κ-caseins) form the major protein fraction of milk, irrespective of their origins. They are able to form well-ordered colloidal structures in association with colloidal calcium phosphate, named casein micelles. Chymosin-mediated milk coagulation takes place through loss of casein micelles' stability by hydrolyzing κ-caseins. This process is critical for the quality of cheese and other milk derivatives. Therefore, many microscopy techniques have been used to understand the structural aspects underlying the integrity of casein micelles during chymosin action. However, these technologies can be costly and laborious. In this study, atomic force microscopy (AFM) and dynamic light scattering (DLS) were used to study milk coagulation by chymosin. Following 15 min of chymosin action, the AFM images showed the start of the formation of casein micelle aggregates. After 30–45 min, the micelles continued aggregating, forming structures such as bunches of grapes. Finally, after 45–60 min, these structures formed large clusters of casein micelles. After 60 min, the zeta potential did not drop to zero when the milk clotted, but still had a negative value, suggesting that the κ-caseins on the micelle surface were not totally hydrolyzed. The results corroborate those previously described and suggest this tool as an alternative to study the milk-clotting process at the ultrastructural level induced by proteases.